Design of functionally cooperating systems and application towards self-propulsive mini-generators. (6th October 2020) - Cheng, Mengjiao; Zhang, Lina; Shi, Feng
Abstract : Progress of 'functionally cooperating systems' is reviewed with emphasis on self-propulsion including design of material systems for applications in mini-generators based on horizontal/vertical motions, self-assembly, and directed transportation. Abstract : The research field of smart materials exhibits a systematic trend with multiple cooperative materials for achieving complex tasks. Recently, the research on 'functionally cooperating systems' has arised as a solution to address this systematic demand, namely, the integration of two or more smart materials into one device to make them function cooperatively for designated missions. In particular, research on the self-propulsion of miniature smart devices via functionally cooperating systems has demonstrated advanced uses such as mini-generators, biomimicking devices, macroscopic supramolecular assembly, and directed transportation. Among them, mini-generators that convert the kinetic energy from motion to electrical energy hold promise for improving the energy diversity with interdisciplinary efforts and achievements owing to the integrated and cooperative characteristics of smart devices. To review the recent progress of functionally cooperating systems, herein, we introduce this research field with emphasis on the demonstration of self-propulsion, summarize the underlying principles for integrating multiple smart materials with typical examples, demonstrate the application of self-propulsive mini-generators based on horizontal/vertical and other reciprocating motions, uses of self-propulsion in macroscopic supramolecular assembly and directed transportation. We believe that an insight into functionally cooperating systems may motivate innovative strategies for the systematic integration of smart materials.